Stress and compressibility calculation in subsoil of high embankments and effectiveness of speeding up subsoil consolidation - Marian Drusa; Nguyen Giang (Communications - Scientific letters of the University of Zilina, 2004)
When designing a project of speeding-up consolidation of subsoil of high embankments, there are some influences that cannot be missed. Especially in geotechnical engineering, we have to work with influences and uncertainties that have origin in geological space and surveying possibilities. On a practical example we present a possible way of subsoil stress and compressibility calculation and influence of different input data on necessary time of 90% consolidation of subsoil of one leg of a high embankment that has impact also on design distance and amount of sand piles or geodrains.